Absolute seat movement in crew boat - Kleshnev, V. (BioRow, 2024)
Did you know that rowers spent an extra 10.5% energy during recovery to overcome inertia? This was found as a ratio of kinetic energy to rower`s Work per Stroke output, and corresponds well to our previous estimation of inertial efficiency (RBN 2010/05).